Portable Paddy Dehusking Machine - K.A Hamzah (Universiti Sains Islam Malaysia, 2024)
Portable Paddy De-husking Machine is invented to assist farmers in paddy processing for personal use or selling in the market. At this moment, farmers need to use a traditional method by using 'lesung-rice' to dehusk the paddy followed by traditional winnowing technique to separate the paddy and bran. Until now, no local company has ever developed this paddy de-husking machine. The harvested paddy needs to be in dry condition before it can be processed in this machine. The brown rice produced by Portable Brown Rice Milling Machine possesses the same quality as the brown rice sold in the market and it can work up to 99.9% efficiency. It is recommended that this machine can be subsidized by government at every district or village for farmers' own use or for marketing purposes.